HTML5 Programming for ASP.NET Developers - Joshi, Bipin; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
HTML5 Programming for ASP.NET Developers teaches you to harness the power and flexibility of HTML5 in your ASP.NET Web Forms and ASP.NET MVC applications. Focusing on the programmable features of HTML5 that will be most useful to you as an ASP.NET developer, this book will take you straight to the heart of what you can get out of this new technology. HTML5 is an emerging web standard that has received a great deal of attention from browser companies and the developer community, encompassing HTML, JavaScript enhancements and CSS3 specifications. But HTML5 isn't just about markup. A major part of HTML5 is its programmable features and APIs, which make up the core of this book. HTML5 Programming for ASP.NET Developers will show you how to: Add interactivity and media to your sites using the Canvas and Audio and Video APIs. Make your web applications work offline, understand client side storage options using web storage, and work with local files using the File API. Use the Communication API and Web Sockets for easier communication between server and client. Other topics include multithreading with Web Workers, understanding the new input types, using Geolocation, and enhancing your web forms and views with CSS3. All major browsers already support HTML5 to varying degrees and are aggressively working to provide full-fledged standardized support. Start using HTML5 in your projects today, and build future-ready web applications that take advantage of the exciting features that HTML5 has to offer.
Keywords: Microsoft software; Microsoft .NET Framework; Software engineering; Microsoft and .NET.; Software Engineering/Programming and Operating Systems